Government Policy on Child Crime Through the Concept of Diversion as a Solution Amid the Spread of Covid-19 - Karsudin, Karsudin; Cahyaningtyas, Irma (Universitas Negeri Semarang, 2021)
This study aims to analyze the concept of diversion as an instrument to realize restorative justice, applied in the Decree of the Minister of Law and Human Rights of the Republic of Indonesia Number M. HH-19. PK.01.04.04 of 2020 Regarding Release and Acquittal of Prisoners and Children Through Assimilation and Integration to Prevent and Control the Spread of Covid-19. The research method used in this research is normative juridical using secondary legal data. Based on the results of the research, it is known that the handling of juvenile criminal cases through the concept of diversion based on restorative justice is carried out to guarantee and respect the dignity of the child, carried out in the best interests of the child and by considering justice for the victim. The government, which is represented by The Minister of Law and Human Rights, has made a very responsive policy through the Decree of the Minister of Law and Human Rights of the Republic of Indonesia Number M. HH-19. PK.01.04.04 of 2020 Regarding Release and Acquittal of Prisoners and Children Through Assimilation and Integration to Prevent and Control the Spread of Covid-19.